Exploring The Motives of Online Dating Application Users - Bramanwidyantari, Maria; Helmi, Avin Fadilla (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Online dating become popular among people who are looking for a romantic relationship possibility. Tinder is one kind of application which originally developed as an online dating platform. As Tinder usage number raised year by year in Indonesia, we aimed to identify the general overview of motivations for using Tinder and examine the differences from certain demographic data. The study was conducted among Indonesian emerging adults who completed an online survey. All the participants have a Tinder account (n = 390). The result has shown that most user motives were related to social compensation, either having romantic partners or acquaintances. Most users are female to relieve boredom and fulfill curiosity motives while male respondents had motives to seek romantic partners. Around 59,50% of respondents not using other online dating apps with the duration of Tinder usage ranging from 15-60 minutes a day. This research shed light on Tinder user four motives categorization along with its demographic condition.